A comparison of the wild food plant use knowledge of ethnic minorities in Naban River Watershed National Nature Reserve, Yunnan, SW China - Ghorbani Abdolbaset; Langenberger Gerhard; Sauerborn Joachim (BMC, 2012)
Abstract Background Wild food plants (WFPs) contribute to the nutrition, economy and even cultural identity of people in many parts of the world. Different factors determine the preference and use of WFPs such as abundance, availability, cultural preference, economic conditions, shortage periods or unsecure food production systems. Understanding these factors and knowing the patterns of selection, use and cultural significance and value of wild food plants for local communities is helpful in setting priorities for conservation and/or domestication of these plants. Thus in this study knowledge of wild food plant use among four groups namely Dai, Lahu, Hani and Mountain Han in Naban River Watershed National Nature Reserve ((NRWNNR), Xishuangbanna were documented and analyzed to find the similarity and difference among their plant use. Methods Data on wild food plant use was collected through freelisting and semi-structured interviews and participatory field collection and direct observation. Botanical plant sample specimens were collected, prepared, dried and identified. Results A total of 173 species and subspecies from 64 families and one species of lichen (Ramalina sp.) are used as WFP. There were differences on the saliency of wild food plant species among four ethnic groups. Consensus analysis revealed that knowledge of wild food plant use for each ethnic group differs from others with some variation in each group. Among informant attributes only age was related with the knowledge of wild food plant use, whereas no significant relationship was found between gender and age*gender and informants knowledge of wild food plant use. Conclusion Wild food plants are still used extensively by local people in the NRWNNR, some of them on a daily base. This diversity of wild food plants provide important source of nutrients for the local communities which much of their caloric intake comes from one or few crops. The results also show the role of ethnicity on the preference and use of wild food plants. There is a big potential for harvesting, participatory domestication and marketing of WFPs especially in the tourism sector in the area.